Combination of iTRAQ proteomics and RNA-seq transcriptomics reveals multiple levels of regulation in phytoplasma-infected Ziziphus jujuba Mill. (27th December 2017) - Ye, Xia; Wang, Huiyu; Chen, Peng; Fu, Bing; Zhang, Mengyang; Li, Jidong; Zheng, Xianbo; Tan, Bin; Feng, Jiancan
Abstract: Jujube witches' broom (JWB) is caused by infection with a phytoplasma. A multi-omics approach was taken during graft infection of jujube by JWB-infected scion through the analysis of the plant transcriptome, proteome and phytohormone levels. A high number of differentially expressed genes (DEGs) were identified 37 weeks after grafting (WAG), followed by observation of typical symptoms of JWB at 48 WAG. At 37 WAG, the majority of the upregulated DEGs and differentially expressed proteins (DEPs) were related to flavonoid biosynthesis, phenylalanine metabolism and phenylpropanoid biosynthesis. Two of the four upregulated proteins were similar to jasmonate-induced protein-like. Among the downregulated genes, the two most populated GO terms were plant–pathogen interaction and plant hormone signal transduction (mainly for tryptophan metabolism). Moreover, phytoplasma infection resulted in reduced auxin content and increased jasmonate content, indicating that auxin and jasmonic acid have important roles in regulating jujube responses during the first and second stages of phytoplasma infection. At 48 WAG, the two largest groups of upregulated genes were involved in phenylpropanoid biosynthesis and flavonoid biosynthesis. Both genes and proteins involved in carbon metabolism and carbon fixation in photosynthetic organisms were downregulated, indicating that photosynthesis was affected by the third stage of phytoplasma infection. Abstract : Plant defense: Secrets of phytoplasma revealed A multi-omics approach sheds light on the mechanisms of infection and defense at play between jujube trees and an enigmatic pathogen. Phytoplasmas are unculturable bacterial parasites discovered only a few decades ago, which cause deformed growths known as 'witch's brooms' in woody plants. A team at Henan Agricultural University, led by Jiancan Feng, explored the mechanisms of phytoplasma infection in the jujube tree ( Ziziphus jujuba ), by grafting healthy trees with infected branches. They employed a multi-pronged approach, analyzing the trees' gene activity, protein production, and hormone levels following infection. Their results suggest that the plant hormones auxin and jasmonic acid play important early roles in response to phytoplasma infection and that, as the witch's broom developed, processes such as photosynthesis were negatively impacted. These findings underpin future research towards preventing this devastating disease.